ACCEPTANCE OF COOKIES SUBSTITUTE OF MILLET FLOUR AND BRAN FLOUR AS PROTEIN ENERGY SOURCES (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2022)
ABSTRACTIntroduction: One of the government's efforts in addressing the problem of underweight in Indonesia is PMT (Supplementary Feeding). As an effort to support government programs, innovations of nutritious and locally substituted PMT are needed. Cookies made from millet and bran can be used as a source of protein-energy for underweight toddlers. Objective: This study aims to determine the production process, quality, and acceptability of the formulation of cookies substituted with millet flour and bran flour. Materials and Methods: The type of this study is descriptive observational. 15 formula cookies were tested through hedonic quality test on 15 trained panelists and also hedonic test on 15 semi-trained panelists. Data processing and analysis were carried out using SPSS with the Kruskall Wallis test, the data were presented in the form of images, tables, and narratives. Result: The process of making cookies is preparing tools and materials, mixing ingredients, weighing and printing dough, baking and cooling. The results of the hedonic quality test on trained panelists were that there were significant differences in the parameters of color, texture, taste and overall with sig.